2013
DOI: 10.1007/s40145-013-0073-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of Li4Ti5O12 synthesized using hydrogen titanate nanowire for hybrid super capacitor

Abstract: Abstract:The electrical characteristics of hybrid super capacitor were evaluated by synthesizing LTO (Li 4 Ti 5 O 12 ) using TiO 2 having a hydrogen titanate nanowire form. Preparation of the hydrogen titanate nanowire was implemented by using TiO 2 having size of 60 nm and NaOH, and performing synthesis at 70 ℃ for 6 h with a sonochemical method. LTO compound was synthesized at 150 ℃ for 36 h and at 180 ℃ for 36 h respectively by using the hydrogen titanate nanowire and LiOH·H 2 O as starting materials with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The hybrid supercapacitors simultaneously store charges by the adsorption/ desorption of PF 6À ion and de/intercalation of Li þ ion at the cathode and anode, respectively. The mechanism for capacitance implementation at both electrodes of the hybrid supercapacitors can be expressed as the following equations [12]:…”
Section: Resultsmentioning
confidence: 99%
“…The hybrid supercapacitors simultaneously store charges by the adsorption/ desorption of PF 6À ion and de/intercalation of Li þ ion at the cathode and anode, respectively. The mechanism for capacitance implementation at both electrodes of the hybrid supercapacitors can be expressed as the following equations [12]:…”
Section: Resultsmentioning
confidence: 99%
“…The resulting LTO nanoparticles thermally treated at 500 °C for 1 h, have an average grain size of about 30–40 nm with excellent phase purity. Kim et al [ 454 ] reported the growth of LTO ceramic from hydrogen titanate nanowires as precursors implemented by using TiO 2 having a size of 60 nm and NaOH, and performing synthesis at 70 °C for 6 h with a sonochemical method. Ghosh et al [ 105 ] reported the sonochemical synthesis carried out using commercial precursors LiOH·H 2 O and TiO 2 (spherical particles of diameter 135 nm) mixed in ethyl alcohol dispersive media.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…The resulting LTO nanoparticles thermally treated at 500 °C for 1 h, have an average grain size of about 30-40 nm with excellent phase purity. Kim et al [454] reported the growth of LTO ceramic from hydrogen titanate nanowires as precursors implemented by using TiO2 having a size of 60 nm and NaOH, and performing…”
Section: Sonochemical Processmentioning
confidence: 99%
“…Since the 1990s, rechargeable lithium-ion batteries (LIBs) have already constituted the most abundant promising energy storage for personal digital assistants (PDA) such as mobile phones or laptops and other devices like electric vehicles (EVs) and unmanned aerial vehicle (UAV) system. [1][2][3][4][5][6][7][8][9][10] The LIBs have the above application prospects stems from their eco-friendliness, low cost, high energy density, and long cycle life. Among all available LIB cathodes, lithium transition metal silicate (Li 2 MSiO 4 ; M = Mn, Fe, Co, Ni) is a stable, cheap, rich, and high-capacity cathode.…”
Section: Introductionmentioning
confidence: 99%